CHARACTERISTICS OF CYTOPROTECTIVE EFFECT ON THE GASTRIC MUCOSA OF CRYOPRESERVED PLACENTA EXTRACT UNDER WATER-IMMOBILIZATION STRESS - Illia Koshurba; Fedir Hladkykh; Mykola Chyzh (Acta Medica Leopoliensia)
Various stressors are currently considered to play a significant role among the etiological factors for development of peptic ulcer disease. Along with psycho-emotional stressing experiences, the causes of formation of stress ulcers include major surgical interventions, thermal or mechanical injuries, severe blood loss, progressive syndrome of endogenous intoxication and more. Among patients in intensive care units, the incidence of stress ulcers is 5.0%, and in 30.0-50.0% of cases stress ulcers are complicated by bleeding and perforation.